The Life Skills Education Program's Effectiveness among students from CBSE and State Boards: An Exploratory Study (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Life skills are adaptable and positive behaviours that help people handle daily life (WHO). It turns knowledge into virtue. Adolescence is crucial to development. Stress and tension accompany the transition from infancy to adulthood. It involves fast physiological and psychological maturity. These are also years of risk-taking, problem-solving, important choices, peer pressures, and stress management. Thus, it marks a life turning point and prospective growth. Physiological, emotional, and sociocultural aspects of teenagers must be addressed. The bigger requirement is to teach teenagers life skills to handle obstacles and demands. Life skills grow dynamically throughout time. One needs numerous talents to handle any event in life every day. Due to their physical and intellectual abilities, adolescents are productive society members. Most teenagers are unable to maximise their potential owing to improper environments. They constantly do antisocial things and ruin their lives. Educational reform should prioritise life skills to make teenagers' lives useful and develop their potential. The researcher compares life skills education for state and CBSE pupils in this report.